2020
DOI: 10.3390/cancers12082274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of T-Cell Exhaustion in Pancreatic Cancer

Abstract: T-cell exhaustion is a phenomenon that represents the dysfunctional state of T cells in chronic infections and cancer and is closely associated with poor prognosis in many cancers. The endogenous T-cell immunity and genetically edited cell therapies (CAR-T) failed to prevent tumor immune evasion. The effector T-cell activity is perturbed by an imbalance between inhibitory and stimulatory signals causing a reprogramming in metabolism and the high levels of multiple inhibitory receptors like programmed cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 208 publications
(284 reference statements)
1
74
0
Order By: Relevance
“…IFN-γ is a major mediator inducing the death of tumor cells. However, continuous exposure to IFN-γ also stimulates tumor cells to express multiple inhibitory modulators including PD-L1 which are majorly enriched in C2 and C3 in our study, thereby suppress the secretion of IFN-γ by effector T cells and result in T cell exhaustion [24,25]. Together, a more prominent feature of immunosuppression may be promoted by these features of C2 and therefore the prognosis of C2 is worse.…”
Section: Discussionmentioning
confidence: 60%
“…IFN-γ is a major mediator inducing the death of tumor cells. However, continuous exposure to IFN-γ also stimulates tumor cells to express multiple inhibitory modulators including PD-L1 which are majorly enriched in C2 and C3 in our study, thereby suppress the secretion of IFN-γ by effector T cells and result in T cell exhaustion [24,25]. Together, a more prominent feature of immunosuppression may be promoted by these features of C2 and therefore the prognosis of C2 is worse.…”
Section: Discussionmentioning
confidence: 60%
“…Lymphocytes are important cellular components of the human immune response system that help to fight tumours by inhibiting cancer cell proliferation, invasion and migration [ 30 ]. Saka et al [ 31 ] reported that T cell exhaustion was closely associated with poor prognosis in cancer. Cholesterol plays a vital role in modulating the activity of membrane proteins, which may be associated with the occurrence and development of cancer and interactions with the body’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth reminding that our results did not contradict previous findings that high infiltration of CD8 + T cells indicated beneficial prognosis, but extended and enriched this conclusion. In the recent literature, tumor with higher CD8 + T cell infiltration, but T cell dysfunction and increased immune escape result in a poor prognosis ( Hossain et al, 2020 ; Saka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%